Development of Interactive e-Modules Based on Socio-Scientific Issues Integrated Micro-Project to Train Students' Understanding of Concepts and Science Process Skills - Alya, Aiza; Purwaningsih, Dyah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop interactive e-modules based on socio-scientific issues integrated micro-projects to train students' understanding of concepts and science process skills on reaction rate material. This method of research is Research and Development (R&D) with a 4-D development model consisting of four stages namely define, design, develop, and disseminate. The data collected includes qualitative data, such as interview results and input regarding the e-module development, and quantitative data in the form of questionnaire scores. The quality of interactive e-modules is assessed based on expert assessments, chemistry teacher assessments, and student assessments. Data analysis techniques involved both qualitative and quantitative methods along with validity assessment criteria. The results of expert assessments of 95.88%, quality assessments by chemistry teachers of 89.1%, and student assessments of 88.2%, obtained high validity results so that it can be concluded that interactive e-modules is feasible to be used in schools on the reaction rate material. The implications of this study suggest that the integration of socio-scientific issues and micro-projects in e-modules can significantly support the improvement of students’ understanding of scientific concepts and their science process skills fostering more meaningful and context-based learning experiences.